2003
DOI: 10.1530/rep.0.1250751
|View full text |Cite
|
Sign up to set email alerts
|

Effects of passive immunization of goats against inhibin on follicular development, hormone profile and ovulation rate

Abstract: This study was conducted to investigate the effect of immunoneutralization against endogenous inhibin on FSH secretion and ovulation rate, with the aim of developing a new superovulation method using inhibin antiserum in goats. Two groups of goats received an i.v. injection of either 10 ml normal goat serum (control; n = 6) or 10 ml inhibin antiserum developed against [Tyr(30)]-inhibin alpha (1-30) (n = 6) 48 h before treatment with prostaglandin F(2alpha) (PGF(2alpha)). Blood samples were collected at 6 h int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 17 publications
3
30
1
Order By: Relevance
“…In addition, the attenuated bacteria vector can also act as a vaccine for Salmonella, which infects both humans and animals, resulting in enteritis and blood poisoning. (Medan et al, 2003a;Sasaki et al, 2006). Our results showed that the recombinant vaccine increased the amount of corpora lutea in rats, consistent with our previous study that the naked inhibin DNA vaccine can augment the twinning rate in sheep and improve litter size in rats (Han et al, 2008).…”
Section: Requirements For An Inhibin Dna Vaccinesupporting
confidence: 92%
“…In addition, the attenuated bacteria vector can also act as a vaccine for Salmonella, which infects both humans and animals, resulting in enteritis and blood poisoning. (Medan et al, 2003a;Sasaki et al, 2006). Our results showed that the recombinant vaccine increased the amount of corpora lutea in rats, consistent with our previous study that the naked inhibin DNA vaccine can augment the twinning rate in sheep and improve litter size in rats (Han et al, 2008).…”
Section: Requirements For An Inhibin Dna Vaccinesupporting
confidence: 92%
“…PGs modulate different ovarian functions, such as the rupture of ovarian follicles associated with ovulation (Husein & Kridli 2003, Medan et al 2003 and luteolysis (Motta et al 1999(Motta et al , 2001. We have previously reported that hyperandrogenism induces a pro-inflammatory status mediated by the PG system in both mice (Luchetti et al 2004, Elia et al 2006 and rats (Amalfi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although activins were initially isolated as gonadal peptides that stimulate FSH secretion (de Jong 1988, Ying 1988, they are now known to be multifunctional growth factors that are very important for vertebrate development and other physiological events , Hillier & Miro 1993, Findlay et al 2001. Inhibins are known to be major FSH-suppressing factors in the female in mammals (Rivier et al 1986, Culler & Negro-Vilar 1989, Kaneko et al 1995, Kishi et al 1999, Medan et al 2003 and are important for determining species-specific ovulation rate . They are mainly expressed in granulosa cells of the ovary in adult cyclic females of various mammals, such as rats (Merchenthaler et al 1987, Meunier et al 1988, golden hamsters (Kishi et al 2002), Siberian hamsters (Phodopus sungorus) (Kenny et al 2002a,b), sheep (Engelhardt et al 1993), pigs (Rokukawa et al 1986), cows (Rokukawa et al 1986), monkeys (Schwall et al 1990) and humans (Merchenthaler et al 1987).…”
Section: Introductionmentioning
confidence: 99%